Feasibility of converting existing residential buildings to net zero-energy buildings in Egypt - Albadry, Somaya (AUC Knowledge Fountain, 2016)
Green architecture, sustainable buildings, environmentally friendly, and other terms have recently become popular in the construction fields among both professionals and non-professionals. Although it is mostly needed and highly feasible, the application of these ideas is not yet at the same level of popularity in Egypt. Researchers are trying to fill this gap by providing different types of recommendations, methodologies, and guidelines to be followed. The aim of this research is to propose a method to be used in solving the energy problem in the building sector in Egypt. Since it is concerned with the existing building stock, the methodology will be addressing retrofitting strategies not new design strategies. The research suggests the nZEB (net zero-energy buildings) methodology as a possible solution for the problem and provides a guideline to be used among the rest of existing building types. The research utilizes energy simulation to validate its initial assumptions and to test the feasibility of the proposed guideline. The final outcome of the research is a method that combines both retrofitting and renewable energy strategies that suit the Egyptian context and potential to convert existing buildings to nZEB buildings. The study starts with the analysis of the current situation of both the existing buildings and the energy sector in Egypt. First, it reviews the classification of the existing building types in the Egyptian context, analyzing the energy consumption patterns and the inefficiencies leading to these patterns, then defining the nZEB concept to familiarize the reader with its different aspects. The empirical part of the study utilizes several cases for a number of prototypes of residential building types in Egypt. Finally, a suggested guideline is applied to an actual existing building and its feasibility is tested by simulation. The research concludes a potential energy saving by applying nZEB strategies to existing residential buildings in Egypt. Future research is required on different building types to validate the nZEB across different building types.